Presepsi peternak terhadap karakteristik teknologi inseminasi buatan di Desa Betikharjo, Kecamatan Semanding, Kabupaten Tuban - Anie Eka Kusumastuti; Dwi Intan Septianai (Jurnal Ilmu Peternakan Terapan, 2023)
This research aims were to determine the profile of beef cattle farmers as well as to identifiy the perceptions of beef cattle farmers on the characteristics of Artificial Insemination (AI) technology based on relative advantage, compatibility, complexity, trialability dan observability in Bektiharjo Village, Semanding District, Tuban Regency from February – March 2023. The research method used was survey method. Data collecting through direct observation, documentation, and interview using structured questionnaire with Likert scale score 1-5. Research sampling chosen purposively using Slovin formula to 85 beef cattle farmers who using AI. Data then analyzed by descriptive analysis. The results showed that the characteristics of majority beef cattle farmers in Bektiharjo Village were aged ranging between 46-55 years old, graduated from elementary school, have around 10-15 years of farming experience with average of 1-5 livestock ownership in a farmer’s household, having average income of IDR 500,000.– IDR 1,000,000.- per month with the main job as a farmer, while breeders as a side job. Beef cattle farmer’s perception of the characteristics of AI technology based on relative advantage, compatibility, complexity, trialability and observability impressions very good/agree in overall. AI technology is very compatible with the previous technology, easy to learn, accepted by beef cattle farmers, very feasible to apply and successfully tested. AI technology applications provides good results in the form of calves that are born having good quality as well as its gave benefits to farmers both of an economic and technical perspective.